P49 UK cost-effectiveness value pyramid of asthma interventions. (12th November 2019) - Roukas, C; Tomini, F; Mihaylova, B
Abstract : Aim: In the UK, the British Thoracic Society (BTS)/Scottish Intercollegiate Guidelines Network (SIGN) and the National Institute for Health and Care Excellence (NICE) have published guidelines for the management of people with asthma. However, although the clinical evidence used for the guidelines development were similar, BTS/SIGN appraised the clinical evidence alone while NICE reviewed also the health economic evidence and supplemented it with further health economic analyses. The aim of this study is to propose a cost-effectiveness value pyramid of asthma interventions in the UK using all available evidence for the additional healthcare cost per an extra quality-adjusted life year (QALY) with different interventions. Method: We followed a three-stage approach. Firstly, the UK-relevant cost-effectiveness findings from economic evaluations of asthma interventions were identified following a systematic review of peer-reviewed economic evaluation studies. Secondly, economic analyses developed or reviewed (e.g. external published studies or pharmaceutical company submissions to NICE) were added. Finally, our review was extended to economic findings for common interventions recommended by BTS/SIGN and NICE in the context of general populations in the absence of results in people with asthma specifically. Results: The totality of available evidence on cost-effectiveness of asthma interventions in UK is presented separately for adolescents/adults (aged 12 years and over) and children (aged 6–14 years). The most cost-effective treatments of interventions with reported ICER<£10, 000 per QALY gained were: smoking cessation interventions and services (ICER £13–£3, 601 per QALY) and flu vaccination uptake (£2, 996–£3, 158), outpatient asthma clinic (£1, 378–£6, 776), specific subcutaneous immunotherapy (£6, 975), ICS+LABA combination inhaler (£7, 604–£13, 706), and temperature-controlled laminar airflow devices (£8, 915) in adults. In children, these were: flu vaccination uptake (£2, 294–£4, 751), specific subcutaneous immunotherapy (£6, 975) and temperature-controlled laminar airflow devices (£8, 915). Conclusions: Lack of cost-effectiveness evidence leads to possible confusion when prioritizing asthma interventions that provide the most benefits for required resources. While our study provides some guidance for highest priority interventions, we have also identified gaps in the cost-effectiveness evidence. Future studies assessing the cost-effectiveness of SABAs, theophylline, oral steroids, immunosuppressant, bronchial thermoplasty, allergy avoidance, exercise and other complimentary therapies are required.